Adaptation, not translation: a 1950s manifesto for translating for children - Wieczorkiewicz, Aleksandra (UCL Press, 2026)
In “The Question of Adaptation“ (1952), Irena Tuwim outlines her approach to translation for young audiences: the far-reaching freedom necessary “for the translator to give linguistic works of the highest quality” and the premise of the translator’s agency and high prestige. Tuwim explicitly proclaims “the rule of adaptation, not translation”; most notably she applied this rule in her translations for children, particularly her much-loved and still much-appreciated translations of A.A. Milne’s “Winnie-the-Pooh“ (“Kubuś Puchatek“, 1938) and “The House at Pooh Corner“ (“Chatka Puchatka“, 1938), often described as “congenial translations” or even better than the originals. This chapter maps out the approach to adaptation from a historical perspective, focusing on the paratexts of Polish translators for children: from F.H. Lewestam’s preface to his translation of Andersen’s fairy tales (1859), in which he proposes – in a similar way to Tuwim – an authorial approach to the text and a cultural translation, through claims challenging adaptation strategies, to the manifesto of the translator of “Winnie-the-Pooh“ and her uses of adaptation. It shows that the translators’ paratexts and commentaries, presenting their self-awareness and implicit theories of translation, have preceded by several decades (or even more than a century) the theoretical reflections of the 1970s, i.e. the time when children’s literature translation studies were established as an academic discipline.
Keywords: Adaptation; Irena Tuwim; Translating for children; Literary translation